1994
DOI: 10.1111/j.1467-8624.1994.tb00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, Teacher, and Child Care History Correlates of Children's Relationships with Peers

Abstract: Mother and teacher correlates of social competence with familiar and unfamiliar peers in 84 children who entered child care at three different times are examined. Social competence at age 4 was assessed with both familiar and unfamiliar peers. Relationships with both initial and 4-year-old teachers were related to social competence with peers. Maternal attachment relationships at 12 months and at 4 years did not predict social competence with peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
69
0
21

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 19 publications
8
69
0
21
Order By: Relevance
“…In contrast, the quality of the teachers` caregiving style showed modest correlations in the expected direction: The more warmly the teacher behaved, the more sympathetic-prosocial and the less avoidant reactions the children showed. Because warmth is a variable that is frequently part of the operationalization of a secure attachment relationship, this result supports the findings of studies conducted within the framework of attachment theory (Howes et al, 1994;Mitchell-Copeland et al, 1997).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In contrast, the quality of the teachers` caregiving style showed modest correlations in the expected direction: The more warmly the teacher behaved, the more sympathetic-prosocial and the less avoidant reactions the children showed. Because warmth is a variable that is frequently part of the operationalization of a secure attachment relationship, this result supports the findings of studies conducted within the framework of attachment theory (Howes et al, 1994;Mitchell-Copeland et al, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…Perhaps the fact that we neither found direct nor moderating effects of the mother-child relationship on the child`s reactions to distress is due to the fact that they were assessed in kindergarten. The effects of the teacher-child relationship could also be explained by a "context effect" because both teacher-child relationship and child`s reactions to distress were measured in the same context, namely the kindergarten (Harris, 1995;Howes et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current findings are consistent with previous research establishing poor childpeer interactions in children without an involved father (Amato & Dorius, 2010;Amato & Keith, 1991;Clarke-Stewart et al, 2000;Crockenberg, 1981;Hetherington et al, 1982;Lopez et al, 2000;Nair & Murray, 2005;Woodward et al, 2000). Additionally, the level of both maternal and paternal attachment security found in the current study was consistent with that measured in previous observational research (Howes, Matheson, & Hamilton, 1994;Lundy, 2002;Nakagawa, Teti, & Lamb, 1992).…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have examined how the quality of the student-teacher relationship relates to children's classroom behavior. Recent research demonstrates that a positive student-teacher relationship characterized by warmth and closeness decreases children's subsequent aggressive behavior in the classroom (Hughes, Cavell, & Jackson, 1999) and is a protective factor for children at risk of behavioral problems (Howes, Matheson, & Hamilton, 1994;Pianta, Steinberg, & Rollins, 1995). Hamre and Pianta (2001) found that kindergarteners whose relationships with teachers were characterized by dependency and low conflict had fewer disciplinary actions and were less likely to be suspended from school through the eighth grade.…”
mentioning
confidence: 99%